Authority Of Government Internal Supervisory Apparatus In Licensing Of Natural Resources To Prevent Corruption, Collusion And Nepotism - Iskandar Iskandar (Universitas Airlangga, 2019)
The occurrence of CCN in the procedure of issuing natural resources licensing is partly caused by the weakness of supervision aspect. In fact, the purpose of supervision is basically intended to prevent the occurrence of CCN. This paper is intended to examine the legal issue of how the regulation of the authority of the government’s internal supervisor (GISA) is in performing the supervisory function based on the prevailing provisions, and how GISA’s authority relates to the supervisory function in the natural resource licensing governance to prevent and eradicate CCN. This is a normative juridical study analyzing the primary and secondary legal materials. The analysis is conducted by qualitative juridical. The result of the study shows that the authority of GISA in performing the function of general and technical supervision has been regulated in various regulations. However, related to appointment in position and responsibility mechanism of execution of task and function of GISA there is still a weakness, as it is done not in stages the results of performance are potentially not objective. The authority of GISA which specifically relates to supervisory functions in natural resource licensing has not explicitly been regulated in the existing regulations. However, GISA remains authorized to monitor the governance of natural resource licensing. Therefore, the issuance of all permit decisions including natural resource licensing is the implementation of government functions, while internal control in the administration of government functions belongs to GISA’s authority.